Male insertion in nursing: what is writing on this question? - Regina Maria dos Santos; Larissa Melo Coêlho Barros; Silvia Alves dos Santos; Wanderlei Barbosa dos Santos; Laís de Miranda Crispim Costa (Universidad de Alicante, 2017)
Study whose objectives were to identify and analyze scientific production about the male insertion in the practice of nursing. This was an integrative review with sample of 47 articles published in national and international databases. The method used was a search strategy where an articulated the keywords with the words AND and OR in different combinations to find as many productions. The results showed four categories: the practice of nursing by men occurred in there ligious context and its physical strength; the feminization of nursing occurred by modernization with Florence Nightingale; it is easier to man in nursing to achieve power positions because of their masculinity and they also exercising the profession for personal fulfillment though they suffer preconception. It was concluded that nursing is still predominantly female but with the male presence gradually increasing. It was observed that for men to integrate into the nursing they develop strategies to overcome the difficulties of being a man and become nurse.